THE IMPACT OF LINGUISTIC RELATIVITY ON TRANSLATION QUALITY (SCIENCE TIME JOURNAL, 2026)
Linguistic relativity, often associated with the Sapir-Whorf hypothesis, suggests that the structure and vocabulary of a language influence its speakers’ perception and cognition. This concept has significant implications for translation, as differences in linguistic systems may affect how meaning is interpreted and conveyed across languages. This article explores the impact of linguistic relativity on translation quality by examining semantic, cultural, and cognitive challenges in translation. It analyzes how translators navigate language-specific concepts, cultural references, and worldview differences to achieve equivalence. The study concludes that while linguistic relativity presents challenges, skilled translators can mitigate its effects through adaptive strategies, cultural competence, and contextual awareness.